Regulation of the proteostasis network by the neuronal system - Zhu, Huadong; Cohen, Ehud (Frontiers in Molecular Biosciences, 2023)
The protein homeostasis (proteostasis) network is a nexus of molecular mechanisms that act in concert to maintain the integrity of the proteome and ensure proper cellular and organismal functionality. Early in life the proteostasis network efficiently preserves the functionality of the proteome, however, as the organism ages, or due to mutations or environmental insults, subsets of inherently unstable proteins misfold and form insoluble aggregates that accrue within the cell. These aberrant protein aggregates jeopardize cellular viability and, in some cases, underlie the development of devastating illnesses. Hence, the accumulation of protein aggregates activates different nodes of the proteostasis network that refold aberrantly folded polypeptides, or direct them for degradation. The proteostasis network apparently functions within the cell, however, a myriad of studies indicate that this nexus of mechanisms are regulated at the organismal level by signaling pathways. It was also discovered that the proteostasis network differentially responds to dissimilar proteotoxic insults by tailoring its response according to the specific challenge that cells encounter. In this mini-review, we delineate the proteostasis-regulating neuronal mechanisms, describe the indications that the proteostasis network differentially responds to distinct proteotoxic challenges, and highlight possible future clinical prospects of these insights.